An evaluation of the Triage Early Warning Score in an urban accident and emergency department in KwaZulu-Natal - D.K. Naidoo; S. Rangiah; S.S. Naidoo (South African Family Practice)
Objective: Triage is an essential first step in the efficient and effective running of any emergency department. A good triage tool saves lives and reduces mortality. The Triage Early Warning Score (TEWS) is a useful tool used to identify patients in emergency departments who are at risk of deterioration and who may require admission. As this triage tool has only been evaluated to a limited extent, this study assessed its effectiveness in identifying patients at risk of early deterioration to enable timely medical intervention.